2010
DOI: 10.1016/j.jamda.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of In-Hospital Mortality Among Hospitalized Nursing Home Residents: An Analysis of the National Hospital Discharge Surveys 2005–2006

Abstract: Objective-To determine the demographic and clinical predictors of in-hospital mortality among hospitalized nursing home (NH) residents. Design-Retrospective Measurements-In-hospital mortality.Methods-A multivariable logistic regression model was developed to determine independent predictors of in-hospital mortality using the 2005 dataset. The model was then applied to the 2006 dataset to determine the generalizability of the predictors.Results-Significant independent predictors of in-hospital mortality in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Published studies have found that admission to hospital is not always to the benefit of these EDPLH patients because admission could aggravate the pre-existing pathological status of these patients [29-31]. It is thus of paramount importance to identify patients at a high risk of dying during hospitalisation before they are actually admitted.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies have found that admission to hospital is not always to the benefit of these EDPLH patients because admission could aggravate the pre-existing pathological status of these patients [29-31]. It is thus of paramount importance to identify patients at a high risk of dying during hospitalisation before they are actually admitted.…”
Section: Discussionmentioning
confidence: 99%
“…22 In a study of hospitalized SNF residents based on National Hospital Discharge Surveys 2005 and 2006, the prevalence of HF was nearly 30%. 2 Similarly, in a 10% random sampling of 1840 SNFs during 2003 to 2004, 37.4% of the 500 322 SNF residents had HF. 17 Their mean age was 81 years, and twothirds were women; 11% were black, 3% were Hispanic, and 1% were Asian.…”
Section: Epidemiology Of Hf In Snfsmentioning
confidence: 99%
“…The precise prevalence of HF among SNF residents is unknown, with estimates ranging between 20% and 37.4%. 2,[16][17][18][19] Of the estimated 1 492 200 Americans (nearly 0.5% of the total US population) living as long-term residents in SNFs, 3 1 317 200 (nearly 90%) were ≥65 years of age, representing nearly 5% of the population aged ≥65 years. More than 70% of these were women, and nearly half were ≥85 years old.…”
Section: Epidemiology Of Hf In Snfsmentioning
confidence: 99%
“…In 2004, the National Nursing Home survey estimated 4.3 % of long-term SNF residents had a primary diagnosis of HF when admitted to their facility [27]. Data derived from the National Hospital Discharge Survey from 2005 to 2006 showed the prevalence of HF among NH patients requiring hospitalization to be near 30 % [28]. The Medicare Payment Advisory Committee (MEDPAC) published a report showing HF prevalence among 1,836,189 SNF stays was 25 % in 2012 [29].…”
Section: Introductionmentioning
confidence: 99%